Formulation and conservation of a pharmaceutical form with leaf extracts from Acacia aroma Gill. ex Hook et Arn - Arias, M. E. (2004)
Leaf fluid extracts of Acacia aroma GILL. ex Hook et Arn showed antibacterial activity against antibiotic multi-resistant bacteria isolated from clinical samples, antioxidant and antiinflammatory activities. Toxicological studies carried out on Artemia salina and Allium cepa attested none toxicity potential. The aim of this work was to elaborate a formulation of topical antibacterial hydrogel with Carbopol acrylic acid polymer containing an A. aroma fluid extract in order to compare with a hydrogel containing commercial antibiotic. The optimal extract concentration in this formulation was determined according to the values of minimal inhibitory concentration and minimal bactericidal concentration for Staphylococcus aureus, methicillin-resistant (F7) and Pseudomonas aeruginosa (F352) . Physical, chemical, rheological and microbiological stability was observed at least during one year. The hydrogel containing Acacia leaves fluid extract shows remarkable antibacterial effect with a broad-spectrum efficacy against Gram positive and Gram negative bacteria at low concentration.